Community and Exclusion: The Torrey Canyon Disaster of 1967. (5th May 2015) - Green, Anna; Cooper, Timothy
Abstract: Oral historians have only recently begun to record the memories of communities affected by major oil spills. In this article we investigate how the first supertanker oil spill in 1967, the Torrey Canyon, is remembered in the coastal communities of Cornwall. Environmental disasters cause more than just environmental damage. They also challenge communities, bringing to the forefront social tensions and conflicts. This study reveals the widespread sense of exclusion within the community as the national political, military and scientific elites took control over the clean-up operation. While aspects of the disaster have been successfully integrated into existing Cornish shipwreck narratives, the displacement of local hierarchies of knowledge by national elites challenged both personal and community identities revealing a subaltern community, often economically vulnerable, whose indigenous knowledge was ignored or devalued. Connecting these dimensions of community memory is the fundamentally moral question of intent, and the resistance to imposed peripheral status enacted through processes of remembering, telling of trickster tales and black humor.